The Agility Analysis of the Ability to Accompany the Ball in Student Football Games - Nur, Muhammad; Awal, Asri; Hafid, Erwan (Sains Global Institut, Indonesia, 2023)
This study aims to determine the Agility Analysis of the Ability to Accompany the Ball in the Football Game of Students of SMK Negeri 4 Jeneponto. This research is a quantitative descriptive research using observation. The method in this study uses descriptive statistics with observation techniques and tests. The population in this study was all students of SMK Negeri 4 Jeneponto as many as 365 students. The sampling technique uses random sampling, so the number of samples in this study was 30 students of SMK Negeri 4 Jeneponto. The test instruments used in this study were agility test instruments and dribbling ability tests in football games. Data analysis uses quantitative description with percentages. the overall data of this study shows that There is a relationship between agility to the ability to accompany the ball in the football game of SMK Negeri 4 Jeneponto students.